Anomalies in the Financial Markets: Reactions of Traders to Information - Jafri, Wafa (2008)
There is empirical evidence available that the trader impact the price of an asset, evidence is also available on the fact that the release of information affects the price of an asset. However, the literature lacks a chain of causation that can capture the role of traders in affecting the price in reference to the release of information in the markets. This paper adapts a causation model explained by Young and Young (2008) to model the role of traders after news has been released into the market. This model is then tested using Monte Carlo Simulations on randomly generated numbers. We find that the calculations of market expectations are redundant and that the number of traders can impact the prices after new information has been made public.